Ovarian Stimulation in Obese and Non-obese Polycystic Ovary Syndrome Using a Low-dose Step-up Regimen with Two Different Starting Doses of Recombinant Follicle-stimulating Hormone - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2008)
Sixty-seven infertile women with polycystic ovary syndrome (PCOS) were divided into two groups, obese and non-obese, according to their body mass index. Waist-to-hip ratio, insulin resistance, total testosterone and dehydroepiandrosterone sulphate levels were significantly elevated in obese, compared with non-obese, patients. Both groups were treated with a low-dose step-up protocol of recombinant follicle-stimulating hormone (rFSH) with a starting dose of 50 IU/day and, every third day, a 25-IU increase in the dose until the appropriate dose was achieved for each individual, up to a maximum of 175 IU/day. In the obese group only, repeat therapy commenced in the second ovulatory cycle in women who had not become pregnant, however a starting dose of 75 IU/day was then used, with incremental and maximum dose as before. The results of the starting dose of 75 IU/day rFSH were compared with the results of a 50 IU/day rFSH starting dose in the obese group. A starting dose of 50 IU/day rFSH in a low-dose step-up regimen was found to be effective, safe and well-tolerated for inducing follicular development in non-obese infertile women with PCOS. However, for obese PCOS patients, a starting dose of 75 IU/day rFSH is recommended.
Keywords: POLYCYSTIC OVARY SYNDROME; RECOMBINANT FOLLICLE-STIMULATING HORMONE; LOW-DOSE STEP-UP REGIMEN; OBESITY; OVULATION INDUCTION; INSULIN-RESISTANCE; OVULATION INDUCTION; WOMEN; GONADOTROPINS